EVALUATION OF LINEAR ACCELERATOR UTILIZATION FOR CA MAMMAE RADIOTHERAPY AT A PRIVATE HOSPITAL - Feliana Mirnawati; Sutopo Patria Jati; Johanes Sugiarto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Radiotherapy is an important cancer therapy in Indonesia. For hospitals which have provided radiotherapy tools for more than five years, they need to evaluate its utilization and influence on patients’ condition.Aim: This study aims to analyze the use of Linac for radiating breast cancers in one of a type-C private hospital in Central Java by using Health Technology Assessment.Method: This study is an observational and descriptive study with an in-depth interview. There were 72 medical record documents examined. Furthermore, the researchers calculated the profits from the financial feasibility of tool investment gained by the hospital. This study involved six Key Informants and four triangulation informants.Results: This study shows that in terms of effectivity aspect, one Linac can prolong patient waiting time about 2-4 weeks. Such a long waiting time may cause disease progression to increase. Meanwhile, seen from the technical characteristics, the tool is not well-maintained by the internal and external parties. It causes the tool’s performance worse. In terms of the economic aspect, the tool has lasted for 7.5 years, but it technically has been utilized for ten years. Therefore, the hospital needs to supply more radiation tools.Conclusion: The Linac utilization in a year increased, and the ca mammae patient visits were high. In addition to those aspects, the profits gained from the health services were high as well. The hospital should add radiation tools to improve the radiation capacity and decrease patient waiting time.Keywords: linac, economic evaluation, Ca Mammae.